Reflectance spectroscopy (0.35–8μm) of ammonium-bearing minerals and qualitative comparison to Ceres-like asteroids - Berg, Breanne L.; Cloutis, Edward A.; Beck, Pierre; Vernazza, Pierre; Bishop, Janice L.; Takir, Driss; Reddy, Vishnu; Applin, Daniel; Mann, Paul (Icarus (New York, N.Y. 1962), 2016)
•A suite of ammonium-bearing minerals was characterized using reflectance spectroscopy.•Diagnostic ammonium absorption bands are present near 1.6, 2.0, 2.2, and 3.1μm.•The positions of these bands are unique to specific ammonium-bearing species. Ammonium-bearing minerals have been suggested to be present on Mars, Ceres, and various asteroids and comets. We undertook a systematic study of the spectral reflectance properties of ammonium-bearing minerals and compounds that have possible planetary relevance (i.e., ammonium carbonates, chlorides, nitrates, oxalates, phosphates, silicates, and sulfates). Various synthetic and natural NH4+-bearing minerals were analyzed using reflectance spectroscopy in the long-wave ultraviolet, visible, near-infrared, and mid-infrared regions (0.35–8μm) in order to identify spectral features characteristic of the NH4+ molecule, and to evaluate if and how these features vary among different species. Mineral phases were confirmed through structural and compositional analyses using X-ray diffraction, X-ray fluorescence, and elemental combustion analysis. Characteristic absorption features associated with NH4 can be seen in the reflectance spectra at wavelengths as short as ∼1μm. In the near-infrared region, the most prominent absorption bands are located near 1.6, 2.0, and 2.2μm. Absorption features characteristic of NH4+ occurred at slightly longer wavelengths in the mineral-bound NH4+ spectra than for free NH4+ for most of the samples. Differences in wavelength position are attributable to various factors, including differences in the type and polarizability of the anion(s) attached to the NH4+, degree and type of hydrogen bonding, molecule symmetry, and cation substitutions. Multiple absorption features, usually three absorption bands, in the mid-infrared region between ∼2.8 and 3.8μm were seen in all but the most NH4-poor sample spectra, and are attributed to fundamentals, combinations, and overtones of stretching and bending vibrations of the NH4+ molecule. These features appear even in reflectance spectra of water-rich samples which exhibit a strong 3μm region water absorption feature. While many of the samples examined in this study have NH4 absorption bands at unique wavelength positions, in order to discriminate between different NH4+-bearing phases, absorption features corresponding to molecules other than NH4+ should be included in spectral analysis. A qualitative comparison of the laboratory results to telescopic spectra of Asteroids 1 Ceres, 10 Hygiea, and 324 Bamberga for the 3μm region demonstrates that a number of NH4-bearing phases are consistent with the observational data in terms of exhibiting an absorption band in the 3.07μm region.